PENGARUH MODEL PEMBELAJARAN PROBLEM BASED LEARNING TERHADAP HASIL BELAJAR IPA SISWA KELAS V B TEMA 6 MATERI PANAS DAN PERPINDAHANNYA DI MI NURUL FALAH KUTOREJO - Faradila, Aisyah; Fauzi, Akhmad (Najah Bestari, 2024)
The problem of low student learning outcomes in science subjects is because students are less focused on paying attention to the teacher's explanations, besides that, when teaching, have not utilized learning models that are appropriate to the class situation. This causes low student learning outcomes. This research aims to determine whether or not there is an influence of the Problem Based Learning learning model on the science learning outcomes of class V B students with theme 6 hot material and its transfer and to find out how much influence the Problem Based Learning learning. Using a quantitative research approach, pre-experimental design, one group pretest-posttest design.There were 21 individuals in the research population. Written tests, or questions, are the method used in this study to collect data. Based on the results of the data analysis that has been carried out, the average result obtained before being given the Problem Based Learning model treatment is 23.47 and the average result after being given the Problem Based Learning model treatment is 78.57, therefore there is an increase of 55.1, then the value after calculating the Normalized Ngain on the average pretest-posttest score obtained an Ngain value of 78.25, this shows in Ngain's percentage was categorized as very affective. This shows that using the Problem Based Learning learning model is very effective in improving the learning outcomes of class V B students on hot material and its transfer at MI Nurul Falah.